Enabling Concurrent Dual Views on Common LCD Screens - Kim, Seokhwan; Cao, Xiang; Zhang, Haimo; Tan, Desney (CHI 2012 Conference on Human Factors in Information Systems, 2012)
Researchers have explored a variety of technologies that enable a single display to simultaneously present different content when viewed from different angles or by different people. These displays provide new functionalities such as personalized views for multiple users, privacy protection, and stereoscopic 3D displays. However, current multi-view displays rely on special hardware, thus significantly limiting their availability to consumers and adoption in everyday scenarios. In this paper, we present a pure software solution (i.e. with no hardware modification) that allows us to present two independent views concurrently on the most widely used and affordable type of LCD screen, namely Twisted Nematic (TN). We achieve this by exploiting a technical limitation of the technology which causes these LCDs to show varying brightness and color depending on the viewing angle. We describe our technical solution as well as demonstrate example applications in everyday scenarios.